Noval advance of histone modification in inflammatory skin diseases and related treatment methods - Zhang, Lichen; Chai, Rongrong; Tai, Zongguang; Miao, Fengze; Shi, Xinwei; Chen, Zhongjian; Zhu, Quangang (Frontiers in Immunology, 2024)
Inflammatory skin diseases are a group of diseases caused by the disruption of skin tissue due to immune system disorders. Histone modification plays a pivotal role in the pathogenesis and treatment of chronic inflammatory skin diseases, encompassing a wide range of conditions, including psoriasis, atopic dermatitis, lupus, systemic sclerosis, contact dermatitis, lichen planus, and alopecia areata. Analyzing histone modification as a significant epigenetic regulatory approach holds great promise for advancing our understanding and managing these complex disorders. Additionally, therapeutic interventions targeting histone modifications have emerged as promising strategies for effectively managing inflammatory skin disorders. This comprehensive review provides an overview of the diverse types of histone modification. We discuss the intricate association between histone modification and prevalent chronic inflammatory skin diseases. We also review current and potential therapeutic approaches that revolve around modulating histone modifications. Finally, we investigated the prospects of research on histone modifications in the context of chronic inflammatory skin diseases, paving the way for innovative therapeutic interventions and improved patient outcomes.